Kompetensi Manajerial dan Kompetensi Supervisi Kepala Sekolah Terhadap Self Supervision Guru MI Ma’arif Bego Sleman - Arif Yuswanto; Suwadi (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan, 2020)
This research starts from a phenomenon that occurs in the world of education, especially related to the competencies of school principals and teaching staff and education staff. While on the other hand, in carrying out their duties still depend on the pattern of organization, leadership, and supervision of the school principal. This has made it unable to provide an assessment of itself based on its capabilities. The study aims to determine the effect of principals 'managerial competencies and principals' competencies as supervisors on teacher self supervision at MI Ma'arif Sambego. Research uses a quantitative approach. Data collection through questionnaires, interviews and documentation. The study population was all teachers in MI Ma'arif Sambego numbering 25 people. The results showed that (1) the School Principal had good managerial competence and was able to organize, plan, and provide direction to the teaching and educational staff. (2) Principal's managerial competence affects the teacher's self supervision in MI Ma'arif Sambego, the results of the study which show the value of p = 0.012 <0.05. (3) The competency of the principal as a supervisor has a high influence on the teacher's self supervision at MI Ma'arif Sambego. the results of the study showed the value of p = 0.010 <0.05. (4) Principal's managerial competence and the principal's competency as a supervisor together (simultaneously) affect the teacher's self supervision in MI Ma'arif Sambego Keywords : Competence, Principal, Self Supervision